Cell of origin and mutation pattern define three clinically distinct classes of sebaceous carcinoma - Jeffrey P. North (Nature Portfolio, 2018)
Sebaceous carcinomas (SeC) are cutaneous malignancies that sometimes metastasize and cause death. Here the authors perform whole-exome sequencing on 32 SeC and report distinct mutational classes that may explain cancer ontogeny and clinical outcome.